"I think they're all basically the same": parents' perceptions of human papilloma virus (HPV) vaccine compared with other adolescent vaccines. (15th March 2016) - Ogunbajo, A.; Hansen, C. E.; North, A. L.; Okoloko, E.; Niccolai, L. M.
Abstract: Background: Human papillomavirus (HPV) vaccination is recommended for routine administration at ages 11–12 years. However, uptake is lower than for other vaccines that are also routinely recommended for adolescents (MCV4 and Tdap). Understanding parental perceptions of HPV vaccine compared with other vaccines may help to inform strategies to increase uptake. Methods: Parents and caregivers ( n  = 45) of adolescents ages 10–18 years from a low‐income, ethnic minority population participated in a qualitative study. Interviews were transcribed verbatim and coded for emergent themes. Results: Many participants perceived the HPV vaccine to be similar to other routine vaccines. Noted similarities included the vaccines' ability to prevent disease, similar methods of administration and belief in health care providers' recommendation. Some parents noted the greater benefit of HPV vaccine in preventing cancer, which was viewed as a serious disease. Parents also noted the different mode of transmission (sexual) for HPV, which evoked mixed opinions. Conclusion: Overall, most participants viewed the HPV vaccine in a positive light and similar to other adolescent vaccines with the added benefit of cancer prevention. Strategies that treat all three vaccines equally such as presenting them similarly as a 'bundle' to parents or considering policy initiatives such as school entry requirements might help increase raise coverage for HPV vaccine.